2009
DOI: 10.1590/s1806-83242009000200004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the diffusion capacity of calcium hydroxide pastes through the dentinal tubules

Abstract: This study aimed to evaluate the diffusion capacity of calcium hydroxide pastes with different vehicles through dentinal tubules. The study was conducted on 60 extracted single-rooted human teeth whose crowns had been removed. The root canals were instrumented and divided into 4 groups according to the vehicle of the calcium hydroxide paste: Group I - distilled water; Group II - propylene glycol; Group III - 0.2% chlorhexidine; Group IV - 2% chlorhexidine. After placement of the root canal dressings, the teeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
24
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 21 publications
5
24
0
1
Order By: Relevance
“…1 The difficulty involved in eliminating microorganisms, as well as their residual presence, warrants the use of root canal dressings after biomechanical preparation. 1 An adequate root canal dressing should have an antimicrobial potential, [2][3][4] the ability to diffuse through dentinal tubules, 1,3,4 biocompatibility, 3,4 and, if possible, the ability to stimulate repair. 3,4 Calcium hydroxide is one of the main root canal dressings used in Endodontics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The difficulty involved in eliminating microorganisms, as well as their residual presence, warrants the use of root canal dressings after biomechanical preparation. 1 An adequate root canal dressing should have an antimicrobial potential, [2][3][4] the ability to diffuse through dentinal tubules, 1,3,4 biocompatibility, 3,4 and, if possible, the ability to stimulate repair. 3,4 Calcium hydroxide is one of the main root canal dressings used in Endodontics.…”
Section: Introductionmentioning
confidence: 99%
“…4 Such vehicles include olive oil, propylene glycol, saline, distilled water, and others. 1,4,[6][7][8] Lage-Marques et al 8 conducted a study to evaluate the rate of ionic dissociation of calcium hydroxide associated to different vehicles-aqueous, viscous, and oily-and concluded that aqueous and viscous vehicles are better suited for paste use.…”
Section: Introductionmentioning
confidence: 99%
“…O tipo e a natureza química do veículo utilizado nas formulações com hidróxido cálcio interferem nas propriedades físico-químicas e biológicas das medicações de uso intracanal e, por conseguinte, também sobre a difusão da medicação na dentina radicular 20,21 . Formulações que contenham a associação de paramonoclorofenol canforado e glicerina ou com digluconato de clorexidina a 2% são as que demonstram maior pH 11,21 .…”
Section: Discussionunclassified
“…In view of this, Ca(OH) 2 powder has been combined with different vehicles, such as distilled water (DW), saline solution, camphorated p-monochlorophenol (CMCP), chlorhexidine, polyethylene glycol, propylene glycol (PG), Otosporin (O), glycerine 12 , and also with chlorhexidine gel [13][14] , in an attempt to improve its antibacterial activity, biocompatibility, speed of ion dissociation and diffusion 11 . Many studies have compared the effectiveness of calcium hydroxide pastes and the use of various vehicles in several respects, namely: the inhibitory behavior towards bacterial infiltration via the crown 15 ; the relationship of each vehicle with the potential for the diffusion of the calcium hydroxide paste into the dentin tubules 16 ; and the degradation of these pastes over the course of time 17 that results in a greater or lesser degree of substantivity and effectiveness against endodontic pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this combination has the objective of improving antibacterial activity and biocompatibility as well as influencing the paste's pH and viscosity and, therefore, facilitating or inhibiting its ion dispersion 11,23 . A number of studies have asserted that the combination of calcium hydroxide with distilled water permits a rapid, efficient dissociation and that paste with propylene glycol has greater viscosity and antimicrobial potential 16 . However, in the present study, pastes that used these substances as a vehicle were unable to produce an inhibition halo in any of the tested strains, corroborating the study by Pacíos et al 19 .…”
mentioning
confidence: 99%